Pay for performance? Government regulation and the structure of compensation contracts - Perry, Tod; Zenner, Marc (Journal of Financial Economics, 2001)
In 1992–1993, the SEC required enhanced disclosure on executive compensation and Congress enacted tax legislation limiting the deductibility of non-performance related compensation over one million dollars, i.e. Internal Revenue Code Section 162(m). We examine the effects of these regulatory changes and report small and large sample evidence that many million-dollar firms have reduced salaries in response to 162(m) and that salary growth rates have declined post-1993 for the firms most likely to be affected by the regulations. We further document that bonus and total compensation payouts are increasingly sensitive to stock returns after 1993, especially for firms with million-dollar pay packages. We also document that, once we control for other factors affecting CEO incentives, the sensitivity of the CEO's wealth to changes in shareholder wealth has increased from 1993 to 1996 for firms with CEOs near or above the million dollar compensation level. Overall, our results suggest that some firms have reduced salaries in response to 162(m). More importantly, the pay for performance sensitivity, measured using total annual compensation and firm-related CEO wealth, has increased for firms likely to be affected by 162(m).